STRATEGI PEMBELAJARAN BERDIFERENSIASI DAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PEMBELAJARAN NILAI-NILAI KEHIDUPAN DALAM CERPEN - Ulfatur Rohmaniyah; Dina Merdeka Citraningrum (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study examines the implementation of the Problem Based Learning (PBL) model in teaching life values explored through short stories to eleventh-grade students. Employing a descriptive qualitative approach, this research elaborates on how PBL is applied to encourage students to identify and analyze life values in literary works. Data was collected through the analysis of lesson plans (RPP) and student learning reflection sheets, and subsequently analyzed using content analysis techniques. The results of the study indicate that PBL effectively facilitates students to become active, collaborative, and critical learners. Through authentic problem-solving, group discussions, and the enactment of short story scenes, students not only identify life values but also develop a deeper and more relevant understanding in relation to their personal experiences. These findings imply that PBL is a potential alternative to replace conventional teacher-centered learning models in literature education, and contributes to the development of innovative learning models for instilling character values.